No LNG: Press Conference and Community Rally - California Coastal Protection Network (California Coastal Protection Network)
Flier, created by CCPN, announcing press conference and community rally to be held on March 10, 2007 at the Malibu pier. Keely Brosnan and assembly members will attend.